1985
DOI: 10.2330/joralbiosci1965.27.1055
|View full text |Cite
|
Sign up to set email alerts
|

Observations on blood capillaries in the rat incisor pulp.

Abstract: Abstract:As revealed by electron microscopy, we observed two types of blood capillaries in the rat incisor peripheral pulp. One was a continuous capillary wall and the other was a fenestrated capillary wall. The former were found chiefly in the basal portion of the incisor and the latter were only in the incisal portion. The continuous capillary may change its configuration into the fenestrated capillary type at the middle portion of the incisor where the odontoblasts are young and the mineralization of dentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…After they reached the predentin border, the proportion of fenestrated capillaries and fenestrated areas in the capillary endothelium increased both in rat incisors (Tabata and Semba, 1985,1987,1990Bishop and Boyde, 1986;Ohshima and Yoshida, 1992) and in rat molars (Yoshida et al, 1988a). In rat incisors, endothelial fenestrations of the odontoblastic capillaries were observed even near the incisal tip, whereas in rat molars, alteration of the odontoblastic capillaries from the fenestrated to the continuous type occurred before withdrawal of the capillaries from the predentin border (Yoshida et al, 1990).…”
Section: Ultrastructural Changes Of Peripheral Capillariesmentioning
confidence: 94%
“…After they reached the predentin border, the proportion of fenestrated capillaries and fenestrated areas in the capillary endothelium increased both in rat incisors (Tabata and Semba, 1985,1987,1990Bishop and Boyde, 1986;Ohshima and Yoshida, 1992) and in rat molars (Yoshida et al, 1988a). In rat incisors, endothelial fenestrations of the odontoblastic capillaries were observed even near the incisal tip, whereas in rat molars, alteration of the odontoblastic capillaries from the fenestrated to the continuous type occurred before withdrawal of the capillaries from the predentin border (Yoshida et al, 1990).…”
Section: Ultrastructural Changes Of Peripheral Capillariesmentioning
confidence: 94%
“…Invasion of terminal pulpal capillaries into the odontoblastic layer has been reported in the rat incisor' , 8,22,23,25), rat molar4'5'8'12), mouse molar7), dog9'16), cat2'6'11), rabbit18) and man15 '19). Among these reports, Bernick (1962)5) demonstrated that the terminal pulpal capillaries gradually withdrew from the predentin border to the odontoblastic-pulpal border with advancing age.…”
Section: Discussionmentioning
confidence: 99%
“…Takahashi et al (1982) examined the developmental changes of the pulpal vessels in the dog by means of vascular casts. Senba et al (1983) and Tabata et al (1985) attempted to divide the rat incisor pulp into several sections and reported the vascular patterns in each section.…”
mentioning
confidence: 99%